Panampaniyaaram": A Traditional Food Product Made with Small- Millet for Revitalization towards Sustainable Nutrition - Subajini, M.; Anushiyaa, A.; Nilukshiya, P.; Rajeenthini, J.; Roxsy, V.; Sanjayan, A.; Tanussalini, S.; Thayalini, T.; Srivijeindran, S. (University of Sri Jayewardenepura, 2024)
The purpose of this research work was to increase the utilization of palmyrah fruit pulp and to obtain a nutritious diet that includes both palmyrah fruit pulp with small-millets by processing it into a value- added natural and traditional food product, "panampaniyaaram". Five series of sensory evaluations performed by panelists using a 9-point hedonic scale were used to assess nineteen treatments on different mixtures by altering the flour types and their percentages in four levels, with palmyrah pulp and small-millet flours, including finger millet, little millet, and Foxtail millet. The sample prepared from 100% finger millet flour was chosen as the most preferred sample, based on the results obtained from the sensory evaluations. Physicochemical analysis of the selected treatment revealed that pH was 5.86±0.01 and the total ash content 1.38±0.18 g/100 g was significantly (p<0.05) higher, and crude fat content 9.04±0.02 g/100 g, total salt content 0.201±0.026 g/100 g, and total sugar content 16.38 g/100 g, was significantly (p<0.05) less than that of the control sample which contained wheat flour. The selected treatment of the mineral content was significantly (p<0.05) higher than that of the control treatment and contained Calcium, Magnesium, Sodium, and Potassium were 150, 60, 32.7 and 76.8 mg/100 g, respectively. In summary, palmyrah fruit pulp and finger millet can be used to create healthy, nutritional and affordable natural snacks "panampaniyaaram", which will satisfy consumer preferences. Further studies are required to understand the developed product's organoleptic properties, antioxidant, vitamins, and anti-microbial activities as well as ways to extend its shelf-life.
Keywords: Panampaniyaaram; Palmyrah pulp; Small-millets; Finger millet; Value-addition